Industrie 4.0: the new industrial revolution. How Europe will succeed - Blanchet, Max; Rinn, Thomas; von Thaden, Georg; de Thieulloy, Georges (Munich, 2014)
"The next revolution with Industry 4.0 represents a huge opportunity for Europe – and it fits the European model. Industry plays a central role in the European economy: It contributes 15% to overall value added and accounts for 80% of innovations and 75% of exports. When taking into account industry-related services as well, industry is the engine of Europe's social economy. But the manufacturing sector has been feeling more and more pressure lately. Due to its declining competitiveness in the face of new market players – particularly from Asia – jobs have been lost in established markets such as the UK ( 29%), France (-20%) and Germany (-8%) over the past 10 years. What's more, countries in Europe are developing differently. While Germany and Eastern Europe continue to increase their share of the industrial market, other EU members are facing de-industrialization. "This development will weaken Europe overall, because more jobs and know-how will be lost in industry. After automation, electrification and digitalization of industry, the introduction of the Internet of Things in the factory marks the advent of a fourth industrial revolution," says Max Blanchet, Partner at Roland Berger Strategy Consultants. However, Europe is much better prepared for this new industrial revolution than many think. In our study entitled "Industry 4.0 – The new industrial revolution – How Europe will succeed," the Roland Berger experts explain what companies and politics should do to support the development of Industry 4.0 and leverage this opportunity for Europe."